Resveratrol Inhibits Enterovirus 71 Replication and Pro-Inflammatory Cytokine Secretion in Rhabdosarcoma Cells through Blocking IKKs/NF-κB Signaling Pathway - Zhang, Li (PLoS One, 2015)
Polydatin and resveratrol, as major active components in Polygonum cuspidatum, have anti-inflammatory, antioxidant and antitumor functions. However, the effect and mechanism of polydatin and resveratrol on enterovirus 71 (EV71) have not been reported. In this study, resveratrol revealed strong antiviral activity on EV71, while polydatin had weak effect. Neither polydatin nor resveratrol exhibited influence on viral attachment. Resveratrol could effectively inhibit the synthesis of EV71/VP1 and the phosphorylation of IKKα, IKKβ, IKKγ, IKBα, NF-κB p50 and NF-κB p65, respectively. Meanwhile, the remarkably increased secretion of IL-6 and TNF-α in EV71-infected rhabdosarcoma (RD) cells could be blocked by resveratrol. These results demonstrated that resveratrol inhibited EV71 replication and cytokine secretion in EV71-infected RD cells through blocking IKKs/NF-κB signaling pathway. Thus, resveratrol may have potent antiviral effect on EV71 infection.